1990
DOI: 10.1063/1.102506
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of epitactically grown GaAs/ErAs/GaAs

Abstract: A series of GaAs/ErAs/GaAs epilayer heterostructures has been grown on (100)GaAs substrates by molecular beam epitaxy and characterized by high-resolution transmission electron microscopy and Rutherford backscattering measurements. Good epitaxy of the ErAs on the GaAs is demonstrated. The top GaAs layer is usually epitactically aligned with ErAs/GaAs in most areas; however, growth of (111)GaAs on (100)ErAs has also been observed. Small grains are present in the top GaAs layer which are twinned on {111} with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…For ErAs depositions thicker than 3 ML the overgrowth of ErAs films with GaAs becomes difficult. 10,11 We believe that these problems are circumvented in the case of ErAs islands because the GaAs overgrowth can seed from the underlying GaAs crystal. 11 As shown in Fig.…”
mentioning
confidence: 99%
“…For ErAs depositions thicker than 3 ML the overgrowth of ErAs films with GaAs becomes difficult. 10,11 We believe that these problems are circumvented in the case of ErAs islands because the GaAs overgrowth can seed from the underlying GaAs crystal. 11 As shown in Fig.…”
mentioning
confidence: 99%
“…2 The chemical and structural stability and compatibility of these compounds with GaAs and their potential for high power device applications have attracted a lot of attention. 3,4 It has been shown that their electrical transport properties are influenced strongly by the magnetism, particularly by spin-disorder scattering. 5 This finding provides renewed stimulus for exploring the magnetic behavior in this system.…”
mentioning
confidence: 99%
“…It should be noted that HREM (Figs. 3,(5)(6)(7)(8)(9) confirms that both interfaces in the GaAs/ Sc,gErO,,As/GaAs epilayers are flat on the atomic scale.…”
Section: Resultsmentioning
confidence: 72%